2007
DOI: 10.1186/1472-6963-7-134
|View full text |Cite
|
Sign up to set email alerts
|

Preventable hospitalization and access to primary health care in an area of Southern Italy

Abstract: Background: Ambulatory care-sensitive conditions (ACSC), such as hypertension, diabetes, chronic heart failure, chronic obstructive pulmonary disease and asthma, are conditions that can be managed with timely and effective outpatient care reducing the need of hospitalization. Avoidable hospitalizations for ACSC have been used to assess access, quality and performance of the primary care delivery system. The aims of this study were to quantify the proportion of avoidable hospital admissions for ACSCs, to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
112
4
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 37 publications
8
112
4
15
Order By: Relevance
“…These conditions are known as Ambulatory Care Sensitive Conditions (ACSCs) and include, as an example, diabetes, respiratory diseases, various cardiovascular diagnoses, and convulsive disorders 36 . The protective effect of GP accessibility and the pattern of GP contact against potentially preventable hospital admissions and adverse health events has been supported by several previous studies 35, [37][38][39][40][41] . As an example, high primary care physician density appears to protect against potentially preventable hospital admissions 35 , whereas lack of a 40 , and lack of access to primary care 41 appear to lead to increase in preventable hospitalisations.…”
Section: Discussionmentioning
confidence: 60%
“…These conditions are known as Ambulatory Care Sensitive Conditions (ACSCs) and include, as an example, diabetes, respiratory diseases, various cardiovascular diagnoses, and convulsive disorders 36 . The protective effect of GP accessibility and the pattern of GP contact against potentially preventable hospital admissions and adverse health events has been supported by several previous studies 35, [37][38][39][40][41] . As an example, high primary care physician density appears to protect against potentially preventable hospital admissions 35 , whereas lack of a 40 , and lack of access to primary care 41 appear to lead to increase in preventable hospitalisations.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, both these definitions identified COPD as an ambulatory care-sensitive condition. Previous studies showed that personal socioeconomic status, 23,29,30 health status, 24,31 and health care access 24,30,32 are associated with avoidable hospitalizations. To the best of our knowledge, however, few studies examined the relationship between COC and avoidable hospitalizations; the majority of these studies included several diseases, [33][34][35] but only 1 study focused on diabetes.…”
mentioning
confidence: 99%
“…23 These conditions also are called ambulatory care-sensitive conditions that could be used to reflect the quality, access, and performance of ambulatory care. 24 To date, many investigators and institutions have identified avoidable hospitalizations using a range of methods. [25][26][27][28] Among these definitions, those defined by the Agency of Healthcare Research and Quality (AHRQ) 28 and by Billings and colleagues 26 were widely used by researchers.…”
mentioning
confidence: 99%
“…Many of these admissions and their associated complications might be prevented through more optimal management of HF in LTC [8][9][10][11][12].…”
mentioning
confidence: 99%